Comparative omasum anatomy in ruminants: Relationships with natural diet, digestive physiology, and general considerations on allometric investigations. (7th January 2019) - Ehrlich, Christian; Codron, Daryl; Hofmann, Reinhold R.; Hummel, Jürgen; Clauss, Marcus
Abstract: The omasum is the third forestomach compartment of pecoran ruminants. It is assumed that the re‐absorption of fluid present in the forestomach digesta (that facilitates particle sorting, digestion, and harvest of microbes) is its main function, so that less diluted digesta is submitted to enzymatic digestion in the lower digestive tract. Here, we evaluate measures of omasum size (representing 84 ruminant species in the largest data set) against body mass and proxies of the natural diet (%grass) or forestomach physiology (fluid throughput), using phylogenetically controlled models. The origin of specimens (free‐ranging or captive) did not have an effect in the data set. Models with the best support invariably either included %grass or a physiology proxy in addition to body mass. These effects were not necessarily additive (affecting the intercept of the allometric regression), but often indicated a change in the allometric body mass‐exponent with diet or physiology. Only models that allowed an influence on the allometric exponent yielded basic exponents compatible with predictions derived from geometry. Species that include more grass in their natural diet, or that have a "cattle‐type" physiology marked by a high forestomach fluid throughput, generally have larger omasa. However, the existence of outliers, as well as the overall data pattern, suggest that this is not an obligatory morphophysiological condition. Circumstantial evidence is presented leading to the hypothesis that the comparatively small and less complex omasa of "moose‐type" species do not necessarily represent an "original" state, but may be derived from more complex states by ontogenetic reduction and fusion of omasal laminae. Abstract : Relationship between the relative parotis gland mass and the relative omasum size (measured as curvature length). Note that the current interpretation of salivary gland size links larger glands to constraints on salivary volume output, that is, relatively smaller glands are thought to achieve a higher saliva flow, hence making a larger omasum for fluid re‐absorption adaptive. Outliers with very small omasa (oribi and blackbuck) and with very large omasa (the Bovini) indicate that the overall pattern is common but not obligatory.